Left-handed Compact MIMO Antenna Array based on Wire Spiral Resonator for 5-GHz Wireless Applications - Alqadami, Abdulrahman Shueai Mohsen; Ping, Jack Soh; Sharul Kamal, Abdul Rahim; Narbudowicz, Adam; Mohd Faizal, Jamlos (Springer Berlin Heidelberg, 2017)
A compact coplanar waveguide-fed multiple-input multiple-output antenna array based on the left-handed wire loaded spiral resonators (SR) is presented. The proposed antenna consists of a 2 × 2 wire SR with two symmetrical microstrip feed lines, each line exciting a 1 × 2 wire SR. Left-handed metamaterial unit cells are placed on its reverse side and arranged in a 2 × 3 array. A reflection coefficient of less than −16 dB and mutual coupling of less than −28 dB are achieved at 5.15 GHz WLAN band.